Analysis of Student Perceptions of Jambi University Biology Education Entrepreneurship - Budiarti, Retni Sulistiyoning; Johari, Asni; Rusdi, Muhammad; Anggereini, Evita (JIPVA (Jurnal Pendidikan IPA Veteran); Vol 7 No 2 (2023): JIPVA (Jurnal Pendidikan IPA Veteran)DO - 10.31331/jipva.v7i2.2944, 2023)
In today's higher education, there is a strong correlation between specialized education and entrepreneurship, and this is highly relevant. This is because entrepreneurship is not just about creating new businesses, but it also involves creativity, problem-solving, leadership, and innovation. The aim of this research is to assist instructors in understanding students' entrepreneurial knowledge in the field of biology education. This study employs a mixed-method exploratory research approach. "Mixed Methods" is a combination method, which is a research approach that integrates or links quantitative and qualitative research methods, while Exploration involves drawing conclusions from the amalgamation of quantitative and qualitative data The sample technique used in this research is purposive sampling. The total number of Biology Education students at Jambi University is 420 and the sample used is 201 students . The result is, the data analysis indicates that students' knowledge of biology concepts applicable to entrepreneurship is positive. Approximately 43.3% of students fall into the "very good" category, and 55.7% fall into the "good" category. This reflects that the majority of students are already aware of the potential application of biology concepts in entrepreneurship. The analysis of students' knowledge in this regard strongly supports further advancement. This isn't limited solely to students majoring in economics; it also applies to Biology Education students who understand that entrepreneurship aligns with the primary goals of Jambi University. Furthermore, the field of biology offers numerous opportunities for economic ventures involving plants and animals.